The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10815-015-0496-0
|View full text |Cite|
|
Sign up to set email alerts
|

PLCζ disruption with complete fertilization failure in normozoospermia

Abstract: Purpose Intracytoplasmic sperm injection (ICSI) is widely used to achieve fertilization in the presence of severe male factor, resulting in high fertilization rates. Nevertheless, 1-3 % of couples experience complete fertilization failure after ICSI. When a male factor is identified, assisted oocyte activation (AOA) can help overcome fertilization failures. The objective of this study is to describe a case of repeated complete fertilization failures after ICSI with donor oocytes, and to investigate the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The role of paternal age in ICSI failure is often hard to analyse in clinical studies 4 5 6 . Investigations into PLCζ protein levels with paternal age would therefore be extremely valuable, as multiple studies show that human sperm with little to no PLCζ expression fail to initiate egg activation 56 57 . Alternatively, zinc has recently emerged as an intriguing potential determinant of egg fertilisation success, sperm-egg fusion inducing a series of ‘zinc sparks’ that occur rapidly in response to Ca 2+ oscillations 58 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of paternal age in ICSI failure is often hard to analyse in clinical studies 4 5 6 . Investigations into PLCζ protein levels with paternal age would therefore be extremely valuable, as multiple studies show that human sperm with little to no PLCζ expression fail to initiate egg activation 56 57 . Alternatively, zinc has recently emerged as an intriguing potential determinant of egg fertilisation success, sperm-egg fusion inducing a series of ‘zinc sparks’ that occur rapidly in response to Ca 2+ oscillations 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (gDNA) was isolated with QIAamp DNA Blood Mini Kit (QIAGEN, Germany) following the manufacturer's instructions. Amplicons of PLCζ were amplified by polymerase chain reaction (PCR) with Phusion HighFidelity DNA polymerase (NEB, USA) using previously described primer pairs [20,21,30].…”
Section: Genomic Analysis Of Plcζmentioning
confidence: 99%
“…Previous studies have shown that failed fertilization after ICSI in some cases of infertile men (i.e., globozoospermic, oligoasthenoteratozoospermic, normozoospermic patients) is related to reduced expression and abnormal localization of PLCζ protein (Azad et al, ; Chithiwala et al, ; Durban et al, ; Lee et al, ; Tavalaee, Nomikos, Lai, & Nasr‐Esfahani, ). Despite the key role of PLCζ in the fertilization process and its potential as biomarker for the ability of sperm to induce oocyte activation, the status of this protein in unexplained infertile (UI) and asthenoteratozoospermic (AT) men remains unclear.…”
Section: Introductionmentioning
confidence: 99%